A network approach for provisional assay recognition of a Hendra virus antibody ELISA: test validation with low sample numbers from infected horses. (May 2018) - Colling, Axel; Lunt, Ross; Bergfeld, Jemma; McNabb, Leanne; Halpin, Kim; Juzva, Susan; Newberry, Kim; Morrissy, Chris; Loomes, Cameron; Warner, Simone; Diallo, Ibrahim; Kirkland, Peter; et al.
Obtaining statistically sound numbers of sera from Hendra virus (HeV)-infected horses is problematic because affected individuals usually die or are euthanized before developing a serum antibody response. As a consequence, test validation becomes a challenge. Our approach is an extension of OIE principles for provisional recognition and included 7 validation panels tested across multiple laboratories that provided estimates for test performance characteristics. At a 0.4 S/P cutoff, 16 of 19 sera from HeV-infected horses gave positive results in the HeV soluble G, indirect ELISA (HeVsG iELISA; DSe 84.2% [95% CI: 60.4–96.6%]); 463 of 477 non-infected horse sera tested negative (DSp 97.1% [95% CI: 95.1–98.4%]). The HeVsG iELISA eliminated almost all false-positive results from the previously used HeV iELISA, with marginally decreased relative sensitivity. Assay robustness was evaluated in inter-laboratory and proficiency testing panels. The HeVsG iELISA is considered to be fit for purpose for serosurveillance and international movement of horses when virus neutralization is used for follow-up testing of positive or inconclusive serum samples.